Analisis Rasio Fundamental dan Good Corporate Governance (GCG) Terhadap Profitabilitas - Amalia Rosdianti; Barlia Annis Syahzuni (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The profitability of mining companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023 was examined using fundamental ratios that could potentially have an impact. Financial ratio analysis is crucial for companies to assess and enhance their profitability in the future. This study considers capital structure, liquidity ratio, activity ratio, and company growth rasio as a fundamental indicators. It also explores how profitability is influenced by good corporate governance disclosure. Five hypotheses were developed to test the impact of fundamental analysis and good corporate governance disclosure on profitability. The study use causal approach and is tested using multiple linear regression analysis. Out of a total population of 112 mining companies, 56 were selected as research samples based on purposive sampling. The regression results indicate that, individually, liquidity and corporate governance disclosure do not significantly affect profitability. However, activity, and company growth each have a significant positive impact on profitability. Meanwhile, only capital structure show a significantly negative value on profitability.